Trigonometric delights - Maor, Eli. (Himayatnagar : Princeton University Press, 2000)
From the earliest known trigonometric table, carved on a clay tablet by an unknown Babylonian scholar, to Fourier's famous theorem, which finally explained the source of musical harmony, here is a rich tapestry of almost four thousand years of trigonometric history.
Includes bibliography and index.
Keywords: Trigonometry. -- Mathematics -- History